Pengembangan Kamus Al-Af’āl dalam Meningkatkan Kemahiran Menulis pada Mahasiswa Prodi Pendidikan Bahasa Arab IAIN Pontianak - Arifudin Arifudin (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2020)
Abstract Many students have difficulty in learning to write which is caused by the absence of a representative learning media. This study aims to create a media that makes it easier for students to find forms of verb changes in Arabic. This research uses Research and development (R&D) design which consists of eight steps: (1) identification of potential and problems, (2) data collection, (3) product design, (4) validation, (5) product revision, (6) small-scale product trials, (7) product revisions, and (8) large-scale use trials. The research data were obtained using interview, documentation and observation techniques. The results of the experts' validation showed that the average percentage rating are 80.47% in terms of media and 84.44% in terms of material. Therefore, the Al-Af’al dictionary is considered very feasible to be used in learning. The results of large-scale trials indicate that Al-Af’al Dictionary media can improve learning outcomes. The results of statistical analysis show that the value of the T test is greater than the T table of 11.03: 2.059, which means there is a significant increase between pre-test and post-test learning outcomes through the use of the Al-Af’al Dictionary. Keywords: Learning Media, Learning Outcomes, Learning to Write